Usando a fórmula: n(AnB)= n(A) + n(B) - n(AuB)
A) sabendo que: n(AnB)=5; n(AuB)=30; n(B)= 15 encontre n(A):
B) sabendo que: n(AnB)=2; n(A)=15; n(B)=10 encontre n(AuB):
Me ajudemmmmmm ❤
Respostas
respondido por:
17
A)
n(A∩B) = n(A) + n(B) - n(AUB)
5 = n(A) + 15 - 30
5 - 15 + 30 = n(A)
20 = n(A)
B)
n(A∩B) = n(A) + n(B) - n(AUB)
2 = 15 + 10 - n(AUB)
n(AUB) = 15 + 10 - 2
n(AUB) = 23
n(A∩B) = n(A) + n(B) - n(AUB)
5 = n(A) + 15 - 30
5 - 15 + 30 = n(A)
20 = n(A)
B)
n(A∩B) = n(A) + n(B) - n(AUB)
2 = 15 + 10 - n(AUB)
n(AUB) = 15 + 10 - 2
n(AUB) = 23
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás